PENGARUH INFUSA DAUN KEPAYANG (Pangium edule Reinw.) TERHADAP PENURUNAN KADAR KOLESTEROL DARAH TIKUS PUTIH JANTAN GALUR WISTAR (Rattus norvegicus) - Mandey, Gloria F. S. Z. (PHARMACON, 2014)
The aims of this research is to determine the influence and relevance of increased doses on infused kepayang leaf (Pangium edule Reinw.) for decreasing the blood cholesterol levels in white male rats (Rattus novergicus). The subject of this study were 15 white male rats weight 130-200 gramme which were divided into 5 groups, consisted of 3 rats for each group. This research used experimental laboratory method with complete randomized design. The results were taken from twice measuring of blood cholesterol which are Pre and Post. Treatment began with a high-fat feeding for 7 days. Pre measuring was done at 8th day. Then treatments were given for each group, aquadest for group A (C-), simvastatin for group B (C+) and infusion of kepayang leaf with each dose for group C (10 g), group D (20 g) and group E (40 g). Post measuring was done at 2 hours then. Data were analyzed by using Paired t-test and One Way ANOVA. The results of statistical analysis didnâ€™t show any significant differences among treatment groups. Consider from the average change and percentage, infusion dose of 40 g kepayang leaf gives the best decrease of blood cholesterol levels. Â Key words : Infusion of kepayang leaf, cholesterol, white male rats